2013
DOI: 10.1093/acprof:oso/9780199253937.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Wealth of Anglo-Saxon England

Abstract: Scandinavian historians. His annotated list of Anglo-Saxon charters, now revised by Susan Kelly, available online and happily known as 'the electronic Sawyer', remains a standard work of reference whilst his publications on the Vikings in both Scandinavia and Western Europe have substantially added to our understanding of the impact of these raiders and traders in the ninth, tenth and 11th centuries. Yet historians tend to be remembered for one piece of work, for good or ill, and in Sawyer's case it is for his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…298 Peter Sawyer has shown that the England of AEthelred's days was a wealthy country and that it might have been this wealth which enticed Scandinavian raiders to loot in the first place. 299 His assumptions regarding the volume of coin production seem to be feasible and concur with Simon Keynes' statement that the sums of tribute mentioned in the Chronicle might be adequate. 300 Apart from that, there seems to be no indication of a steady level of devaluation due to the payments of tribute to the Vikings, but a series of rise and fall in the weight standard.…”
Section: Coins Aethelred's Coinssupporting
confidence: 57%
“…298 Peter Sawyer has shown that the England of AEthelred's days was a wealthy country and that it might have been this wealth which enticed Scandinavian raiders to loot in the first place. 299 His assumptions regarding the volume of coin production seem to be feasible and concur with Simon Keynes' statement that the sums of tribute mentioned in the Chronicle might be adequate. 300 Apart from that, there seems to be no indication of a steady level of devaluation due to the payments of tribute to the Vikings, but a series of rise and fall in the weight standard.…”
Section: Coins Aethelred's Coinssupporting
confidence: 57%
“…160 Sawyer credits this overwhelming quantity of stimulus-cash with being the prime reason for the Danelaw's tenth-century economic boom. 161 The boroughs of the Danelaw became hubs of trade and particularly of manufacturing, making them some of the wealthiest towns in England. 162 Likewise, urban archaeology has revealed that towns like Lincoln, Norwich, Stamford, Thetford and York were some of the largest in England by 1066 and that their economic expansion and urban growth likely began under Scandinavian rule.…”
Section: B U Y I N G I N T O L a Wmentioning
confidence: 99%
“…162 Likewise, urban archaeology has revealed that towns like Lincoln, Norwich, Stamford, Thetford and York were some of the largest in England by 1066 and that their economic expansion and urban growth likely began under Scandinavian rule. 163 Considering this emphasis on cash and that wealth was likely especially concentrated in the hands of those near the top of the Danelaw social hierarchy, the legal system in these areas could have been designed to privilege these elites, creating cash-heavy criminal justice practices like lahcop. Overall, the entire ordealfocused protocol for 'accusation-busy men' in the Wantage Code, including arrangements for counterfeiters, seems to be a West Saxon concept, now being extended from Bromdune-enactment to the Danelaw.…”
Section: B U Y I N G I N T O L a Wmentioning
confidence: 99%
“…This was certainly Sawyer's conclusion about these early raids, noting that they were mostly in the west, 'probably by warriors from Dublin and other bases around the Irish Sea.' 11 Despite this the Norman connection to the raids has prevailed among scholars. For instance, Levi Roach, having referred to the raids of the 980s as 'small-scale affairs' and arguing that coinage shows that AEthelred was not unduly affected by these raids, still put the treaty into this traditional context.…”
mentioning
confidence: 99%